Severely infected pneumoceles of the frontal sinus in patients with mental retardation and brain atrophy treated by endoscopic sinus surgery. Issue 2 (April 2018) - Tojima, Ichiro; Kikuoka, Hirotaka; Ogawa, Takao; Shimizu, Takeshi
Abstract: We herein present three cases of abnormally expanded frontal sinuses (pneumoceles) with severe infection in patients with mental retardation and brain atrophy. Two patients previously underwent laryngotracheal separation surgery, and bacteriological examinations of purulent nasal discharge revealed infections caused by drug-resistant bacteria such as Pseudomonas aeruginosa and Acinetobacter baumannii . As conservative medical treatments were ineffective, all three patients were treated by computed tomography-guided endoscopic sinus surgery. This navigation system is useful for safer surgery in the area of anatomic deformity. The clinical findings, possible etiologies and surgical treatment of these cases are discussed.